[Data] Multi-resonant open-access microcavity arrays for light matter interaction - Doherty, T H; Kuhn, A; Kassa, E (University of Oxford, 2023)
Data presented and analysed in arXiv:2207.03676 [physics.optics] [https://arxiv.org/abs/2207.03676].